Sculpture on the tope of Dhamek,' an engraving by E. Therond, from... - Louis Rousselet (Wikimedia Commons, 1878)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Licence Public domain via Wikimedia Commons
Keywords: Histoire; iconographie; gravure; photographie; Wikimedia Commons